Housing Market Dynamics. On the Contribution of Income Shocks and Credit Constraints - Sven Rady; François Ortalo-Magné (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2001)
This paper presents a dynamic theory of housing market fluctuations. It develops a life-cycle model where households are heterogeneous with respect to income and preferences, and mortgage lending is restricted by a down-payment requirement. The market interaction of young credit-constrained households with older or richer unconstrained households generates the following results. (1) Current income of young credit-constrained households affects housing prices independently of aggregate income. (2) Housing prices and the number of housing transactions are positively correlated. (3) Housing prices over-react to income shocks. (4) A relaxation of the down-payment constraint triggers a boom-bust cycle. These results are consistent with patterns observed in the US and the UK.
urn:nbn:de:bvb:19-epub-20-9
Keywords: E32; G12; G21; R21; 330; Housing Demand; Income Fluctuations; Overlapping Generations; Collateral Constraint